An open‐label study to evaluate the long‐term safety and efficacy of lanadelumab for prevention of attacks in hereditary angioedema: design of the HELP study extension. Issue 1 (6th October 2017) - Riedl, Marc A.; Bernstein, Jonathan A.; Craig, Timothy; Banerji, Aleena; Magerl, Markus; Cicardi, Marco; Longhurst, Hilary J.; Shennak, Mustafa M.; Yang, William H.; Schranz, Jennifer; Baptista, Jovanna; Busse, Paula J.
Abstract: Background: Hereditary angioedema (HAE) is characterized by recurrent attacks of subcutaneous or submucosal edema. Attacks are unpredictable, debilitating, and have a significant impact on quality of life. Patients may be prescribed prophylactic therapy to prevent angioedema attacks. Current prophylactic treatments may be difficult to administer (i.e., intravenously), require frequent administrations or are not well tolerated, and breakthrough attacks may still occur frequently. Lanadelumab is a subcutaneously‐administered monoclonal antibody inhibitor of plasma kallikrein in clinical development for prophylaxis of hereditary angioedema attacks. A Phase 1b study supported its efficacy in preventing attacks. A Phase 3, randomized, double‐blind, placebo‐controlled, parallel‐arm study has been completed and an open‐label extension is currently ongoing. Methods/design: The primary objective of the open‐label extension is to evaluate the long‐term safety of repeated subcutaneous administrations of lanadelumab in patients with type I/II HAE. Secondary objectives include evaluation of efficacy and time to first angioedema attack to determine outer bounds of the dosing interval. The study will also evaluate immunogenicity, pharmacokinetics/pharmacodynamics, quality of life, characteristics of breakthrough attacks, ease of self‐administration, and safety/efficacy in patients who switch to lanadelumab from another prophylactic therapy. The open‐label extension will enroll patients who completed the double‐blind study ("rollover patients") and those who did not participate in the double‐blind study ("non‐rollover patients"), which includes patients who may or may not be currently using another prophylactic therapy. Rollover patients will receive a single 300 mg dose of lanadelumab on Day 0 and the second dose after the patient's first confirmed angioedema attack. Thereafter, lanadelumab will be administered every 2 weeks. Non‐rollover patients will receive 300 mg lanadelumab every 2 weeks regardless of the first attack. All patients will receive their last dose on Day 350 (maximum of 26 doses), and will then undergo a 4‐week follow‐up. Discussion: Prevention of attacks can reduce the burden of illness associated with HAE. Prophylactic therapy requires extended, repeated dosing and the results of this study will provide important data on the long‐term safety and efficacy of lanadelumab, a monoclonal antibody inhibitor of plasma kallikrein for subcutaneous administration for the treatment of HAE. Trial registration NCT02741596